A new method for void fraction measurement of gas–liquid two-phase flow in millimeter-scale pipe. (June 2015) - Zhou, Ying; Huang, Zhiyao; Wang, Baoliang; Ji, Haifeng; Li, Haiqing
Highlights: A new void fraction measurement method is proposed. Relationship between conductance value and void fraction is investigated. Void fraction measurement absolute error is less than 7%. Abstract: This work attempts to investigate the feasibility and potential of Capacitively Coupled Contactless Conductivity Detection (C 4 D) technique in the void fraction measurement of gas–liquid two-phase flow in millimeter-scale pipe and hence to propose a new void fraction measurement method based on C 4 D technique. A new C 4 D sensor is developed and a void fraction measurement system is constructed. As a preliminary study, the research work is focused on the void fraction measurement of two typical flow patterns (bubble flow and slug flow) in millimeter-scale horizontal pipe. The relationship between the conductance value and the void fraction is investigated. It is found that there is obvious linear relationship between the conductance value and the void fraction and flow pattern has significant influence on void fraction measurement. To overcome the influence of flow pattern, different void fraction measurement models are developed for different flow patterns. In the practical void fraction measurement process, flow pattern is firstly identified, then a corresponding void fraction measurement model is selected, and finally the void fraction measurement is implemented with the selected model and the conductance measurement obtained by the new C 4 D sensor. Void fraction measurement experiments are carried out (the inner diameters of the pipes are 2.8 mm, 3.9 mm, 5.3 mm and 7.0 mm, respectively). The experiment results show that the application of C 4 D technique to the void fraction measurement of gas–liquid two-phase flow in millimeter-scale pipe is feasible. The proposed void fraction measurement method is effective and the measurement performance is satisfactory (the maximum absolute error of void fraction measurement is less than 7%). The research results also indicate that C 4 D technique may have a broad application prospective and potential in the research field of two-phase flow.